2014
DOI: 10.1007/978-3-319-07863-2_2
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Learning Support System for Source Code Reading Comprehension

Abstract: Abstract. In this paper, we describe the development of a support system that facilitates the process of learning computer programming through the reading of computer program source code. Reading code consists of two steps: reading comprehension and meaning deduction. In this study, we developed a tool that supports the comprehension of a program's reading. The tool is equipped with an error visualization function that illustrates a learner's mistakes and makes them aware of their errors. We conducted experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 4 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…As a remarkable effort, a framework on reading source code was proposed [5]. Next, Arai et al developed a learning support system for programming beginners that facilitates the process of learning by reading source code, and confirmed that the system was effective [6]. Tang developed a distributed, social code review tool designed for the specific constraints and goals of a programming course named "Caesar" [7].…”
Section: Related Workmentioning
confidence: 99%
“…As a remarkable effort, a framework on reading source code was proposed [5]. Next, Arai et al developed a learning support system for programming beginners that facilitates the process of learning by reading source code, and confirmed that the system was effective [6]. Tang developed a distributed, social code review tool designed for the specific constraints and goals of a programming course named "Caesar" [7].…”
Section: Related Workmentioning
confidence: 99%